Handbook of Plant Biotechnology 2004
DOI: 10.1002/0470869143.kc031
|View full text |Cite
|
Sign up to set email alerts
|

Male Sterility and Hybrid Production Systems

Abstract: The ability to exploit the long known phenomenon of hybrid vigor or heterosis, the superior performance of the F1 hybrid compared to either parent line, has greatly impacted the goal of production agriculture to meet world food demands. Hybrid production systems rely on an efficient and effective mechanism for inducing male sterility in one of the parental lines in order to ensure purity of the resultant hybrid seed. Natural male sterility systems are available but are limited in their availability for all cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Pollen-and seed-mediated transgene flow is difficult to control (Heuberger et al, 2010;Luo et al, 2007). It has been reported that pollen and seeds from poplar (P. trichocarpa) can be easily dispersed over long distances via wind, increasing the risk potential for transgene flow (DiFazio et al, 2012;Kausch et al, 2010;Oliver, 2004;Slavov et al, 2009;Zhang et al, 2012). In addition, pollen from poplar can induce allergic reactions in a large segment of the population (C ß elik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen-and seed-mediated transgene flow is difficult to control (Heuberger et al, 2010;Luo et al, 2007). It has been reported that pollen and seeds from poplar (P. trichocarpa) can be easily dispersed over long distances via wind, increasing the risk potential for transgene flow (DiFazio et al, 2012;Kausch et al, 2010;Oliver, 2004;Slavov et al, 2009;Zhang et al, 2012). In addition, pollen from poplar can induce allergic reactions in a large segment of the population (C ß elik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pollen from poplar can induce allergic reactions in a large segment of the population (C ß elik et al, 2005). As vegetative propagation is preferred over sexual reproduction for most commercial cultivars of poplar, engineering flowerless poplar could provide an effective means to address pollen-and seed-mediated transgene flow and allergy problems (DiFazio et al, 2012;Kausch et al, 2010;Oliver, 2004;Zhang et al, 2012). Furthermore, with reproductive organs eliminated, more photosynthetic products can be used for vegetative growth, likely leading to improvement of biomass production.…”
Section: Introductionmentioning
confidence: 99%